Multi-copy gene family evolution on the avian W chromosome - Rogers, TF; Pizzari, T; Wright, AE (Oxford University Press, 2021)
The sex chromosomes often follow unusual evolutionary trajectories. In particular, the sex-limited Y and W chromosomes frequently exhibit a small but unusual gene content in numerous species, where many genes have undergone massive gene amplification. The reasons for this remain elusive with a number of recent studies implicating meiotic drive, sperm competition, genetic drift and gene conversion in the expansion of gene families. However, our understanding is primarily based on Y chromosome studies as few studies have systematically tested for copy number variation on W chromosomes. Here, we conduct a comprehensive investigation into the abundance, variability, and evolution of ampliconic genes on the avian W. First, we quantified gene copy number and variability across the duck W chromosome. We find a limited number of gene families as well as conservation in W-linked gene copy number across duck breeds, indicating that gene amplification may not be such a general feature of sex chromosome evolution as Y studies would initially suggest. Next, we investigate the evolution of HINTW, a prominent ampliconic gene family hypothesized to play a role in female reproduction and oogenesis. In particular, we investigate the factors driving the expansion of HINTW using contrasts between modern chicken and duck breeds selected for different female-specific selection regimes and their wild ancestors. Although we find the potential for selection related to fecundity in explaining small-scale gene amplification of HINTW in the chicken, purifying selection seems to be the dominant mode of evolution in the duck. Together, this challenges the assumption that HINTW is key for female fecundity across the avian phylogeny.